OPTIMIZATION OPERATION MANAGEMENT FOR RIAM KANAN HYDROPOWER DAM TO MEET WATER RESOURCES RATE DEMAND IN BANJAR BAKULA WATER SUPPLY SYSTEM - PDAM INTAN BANJAR, SOUTH BORNEO (2010-2030) - DINAHKANDY (NIM : 25312033), IRMA
Based on the reviews masterplan of Intan Banjar Regional Drinking Water Company, drinking water needs of the main zone is 1346 lps at 2030. To increase coverage and a water supply and ensure the future water availability, Riam Kanan hydropower dam can be made as an alternative source of raw water. The allocation for drinking water use probable drought discharges with a return period 10-20 years of Riam Kanan dam which is worth 11.9 to 16.3 m3/s. Management of Riam Kanan dam is planned to meet the main needs as hydropower and needs in the downstream of 12.56 m3/s. Riam Kanan dam investigation with a discharge capacity of reservoir inflow 1990-2012 showed that the reservoir is operated by wet policy of 5 years and an effective volume amounted to 326.1 hm3. Deterministic dam management using average with a return period of 5 years for trajectory (dry, normal, wet) is less adaptive because it is still a lot of water is wasted. Correlation of continuous discharge forecasting with historical debit is 0.86, while the correlation of discrete Markov discharge forecasting with historical discharge is 0.72 so that a continuous discharge forecasting considered to be more adaptive to the historical discharge. Optimal dam management using continuous models have a correlation coefficient of 0.93 to the actual trajectory while using discrete Markov models of 0.89, so that the continuous model was chosen to be a model for the most optimal operation of Riam Kanan dam to fulfill the demands in the downstream.